The Textological Analysis of the Qur’anic Manuscript Written by Syekh Muhammad Said Ranah Kumpai Kampar Riau - Putra, Afriadi; Yasir, Muhammad; Lukmanul Hakim; Wendy Hermawan (DINIKA : Academic Journal of Islamic Studies, 2023)
This article examines a manuscript of the Qur'anic mushaf inherited from Sheikh Muhammad Said Ranah Kumpai (1885), from Riau, written around 1850. This article focuses on two aspects, namely, describing the type of writing and reading used in the manuscript and then comparing it with the writing and reading of other manuscripts that were contemporary with it or with the current Indonesian Standard Mushaf. Using a philological approach, this study shows that the manuscripts of Sheikh Muhammad Said were written using a mixed rasm between Usmani and Imlai. One of the factors is because the habits of the people of the archipelago at that time were stronger with oral traditions. On the other hand, the use of Usmani rasm in the Mushaf has not been a deep concern in copying the Mushaf. The qiraat used is the qiraat of Imam 'Ashim from narration of Hafs, although there are some marginal notes on certain words that can be read with other readings.